2022
DOI: 10.1093/mnras/stac1187
|View full text |Cite
|
Sign up to set email alerts
|

A unified model for the evolution of cataclysmic variables

Abstract: We give an updated version of the analytical equation of state used in the Cambridge stellar evolution code (STARS) as a free to use open-source package that we have used to model cool white dwarfs down to temperatures log10(Teff/K) = 3. With this update in the STARS code we model the secular evolution of cataclysmic variable (CV) stars using a double dynamo model wherein there is an interplay between two α − Ω dynamos, one in the convective envelope and the other at the boundary of a slowly rotating shrinking… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 23 publications
0
4
0
Order By: Relevance
“…We note importantly that no unique M 2,gap exists for all CVs, as is known from observations and theoretical computations (e.g. Knigge et al 2011;Sarkar & Tout 2022). This is because for unevolved CV donors, M 2,gap and the lower end of the period gap, at which mass transfer resumes (P gap,− ), depend on M 1 and the MB strength above the period gap.…”
Section: Binary Evolution Calculationmentioning
confidence: 69%
“…We note importantly that no unique M 2,gap exists for all CVs, as is known from observations and theoretical computations (e.g. Knigge et al 2011;Sarkar & Tout 2022). This is because for unevolved CV donors, M 2,gap and the lower end of the period gap, at which mass transfer resumes (P gap,− ), depend on M 1 and the MB strength above the period gap.…”
Section: Binary Evolution Calculationmentioning
confidence: 69%
“…We have used a physically motivated formalism for this magnetic braking mechanism, discussed in detail by Sarkar & Tout (2022), known as the double dynamo (DD) model, and compared it to the empirical magnetic braking formulae of Rappaport et al (1983) and its modification by Knigge et al (2011). We show that the time-scales of angular momentum loss and subsequent mass loss are shorter with the DD model than with the other two models.…”
Section: Discussionmentioning
confidence: 99%
“…The first is that of Sarkar & Tout (2022). We use their formula for AML by magnetic braking, AML MB , their equation ( 25), with the three free parameters (𝛼, 𝛽, 𝛾) = (4.6, 0.08, 3.2) 1 .…”
Section: The Dependence Of the Secular Evolution Of CV Systems On The...mentioning
confidence: 99%
“…(5) Population studies based on the standard evolutionary model predict spatial densities 1-2 orders of magnitude larger than observed values (Zorotovic & Schreiber 2020). Although additional angular momentum loss mechanisms and models (Patterson 1998;Knigge et al 2011;Schreiber et al 2016;Pala et al 2017;Zorotovic & Schreiber 2017Belloni et al 2018;Liu & Li 2019;Metzger et al 2021;Sarkar & Tout 2022) were suggested to solve the disagreements, the only published, self-consistent simulations of CV evolution were performed by Hillman et al (2020), whose multigigayear models of novae take into account every nova eruption's thermonuclear runaway, mass and angular momentum losses, feedback due to irradiation, variable mass transfer rate (M  ), orbital size, and period changes. Hillman et al (2020) reproduced the observed range of mass transfer rates at a given orbital period, with large and cyclic kiloyear to megayear timescale changes.…”
Section: Introductionmentioning
confidence: 99%